COOPERATION AMONG THE SCO COUNTRIES IN THE HUMANITARIAN SPHERE: EXISTING PROBLEMS AND POSSIBLE SOLUTIONS - MOROZOV, Yuri (CENTRAL ASIA AND THE CAUCASUS, 2009)
The humanitarian aspect is just as important as the economic and political components of the state’s activity in terms of ensuring national interests at the international level. The concept “international humanitarian cooperation” includes interstate cooperation in cultural, scientific, information, sport, tourism, and other issues1 and serves both individual and universal interests. No state can develop in an unfavorable environment without a high level of medical and educational development that guarantees people a dignified standard of living. Full-fledged humanitarian interaction can only develop in an atmosphere of trust and friendship among nations and helps, in turn, to gradually remove any negative perceptions of other national cultures from people’s minds. The culture of society as a whole and its tolerance toward other nationalities presuppose that a nation stands psychologically strong against such contemporary problems of mankind as terrorism and extremism and make it possible to resolve them by peaceful means. Humanitarian cooperation is also of application-oriented relevance. For example, the knowledge of language, culture, and traditions of another nation make it possible for states to interact more successfully in order to ensure security. Recognizing the importance of humanitarian cooperation, national power structures and international organizations are investing large amounts of money in its development. Many states are practicing the policy of “cultural diplomacy,” which envisages exporting their culture abroad, working with compatriots living in other countries, and hiring foreigners, thus pursuing the goal of creating a positive image for the country and raising its authority at the international level. For example, Germany allots impressive funds for this purpose—in 2008, 658.1 million euros, or 23% of the Foreign Ministry’s budget, were spent to this end.2 Unfortunately, the Russian government underestimates the importance of this vector in the state’s activity. When comparing the different approaches to the humanitarian sphere, we will take a look at the possible ways to raise efficiency and improve cultural cooperation within the framework of the SCO.